计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 09:16:37
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=计算(a-b)^m(a-
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m
=(a-b)[-8(a-b)^3](a-b)^10
=-8(a-b)^14
计算:(b-a)^5(a-b)^m+(a-b)^(m+3)(b-a)^2
计算:(a-b)^m+3(b-a)^2(a-b)^m(b-a)^5
计算:(a-b)^(m)*(a-b)^(2)*[2(b-a)]^3*[(b-a)^(5)]^(2)/(a-b)^(m).
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
计算(-a^m*b^n)^2=
计算a+b/b-a-b/b
计算:m分之a+b+m分之a-b
计算:((a+b)(a-b)-(a-b)^2+2b(a-b))/4(a-b)
计算·[(2a+-b)/(a+b)-b/(a+b)]/(a-2b)/(a+b)
(a-b)^m+3(b-a)^2(a-b)^m
计算:(2)(b-a)^2(a-b)
计算(b+2a)(2a-b)
计算(a-b)(a+2b)
计算(a+b)(a-2b)
(a+b+1)(2a-b)计算
计算:(a+b)(2a-3b)
计算(a-b)(a^2-b^2)(a+b)
计算(a-b)(b-a)^3+[(a-b)^2]^2